Techno-economic-assessment of the methanol synthesis from captured CO2 and modular nuclear power-based electrolysis - Marcello Maria Bozzini; Margherita Signorelli; Emanuele Moioli; Flavio Manenti (Journal of CO2 Utilization)
Recently, several technical and political efforts targeted the reduction of CO2 levels in the at- mosphere, accompanied by a strong incentivization of carbon-neutral fuel production. In this context, a methanol synthesis plant using H2 originated from electrolysis powered with nuclear energy from fourth-generation micro-modular reactors is proposed here. This latest generation of nuclear reactors aims to transform the energy sector by enhancing the scalability, efficiency, safety, and sustainability of nuclear power. Prefabricated plants can be easily transported and installed at lower costs and with more flexibility, enabling an easier integration with chemi- cal plants. The purpose of this work is to perform an eco-techno-economic assessment of the methanol production fueled by nuclear-power-driven electrolysis and captured CO2. The re- search involves the assessment of the integration of the methanol plant with various technologies for capturing and utilizing CO2 (Direct Air Capture, Carbon Capture of flue gases, or utilizing cheap CO2 from companies). The analysis emphasizes the positive impact of the coupling of electricity production, chemical synthesis and carbon capture in reducing greenhouse gas emis- sions and improving energy efficiency. The findings indicate that the integration of methanol synthesis with carbon capture presents considerable environmental benefits in comparison to tra- ditional methanol plants. Significant reductions compared to state of the art in CO2 emissions were observed, ranging from −0.94 to −1.06 kgCO2-eq/kgMeOH of the proposed technologies, in contrast to the 0.5–4.3 kgCO2-eq/kgMeOH range for traditional plants. The economic analysis showed that the levelized cost of methanol production is 1809$ per ton in the worst-case scenario with DAC, and 1381$ and 1283$ per ton with CCU and benchmark technologies, respectively. These values are expected to decrease with the technological advances. Reducing the CapEx (of the DAC unit and nuclear batteries) and incorporating additional energy optimizations are the main drivers of the further enhancement of the economic competitiveness of the process.